An E-box Motif Residing in the Exon/Intron 1 Junction Regulates Both Transcriptional Activation and Splicing of the Human Norepinephrine Transporter Gene - Kim, Chun-Hyung; Ardayfio, Paul; Kim, Kwang-Soo (The Journal of biological chemistry, 2001)
The norepinephrine transporter (NET) is responsible for the rapid NaCl-dependent uptake of norepinephrine into presynaptic noradrenergic nerve endings. Recently, we have characterized the structural organization of the 5â² upstream promoter region of the human NET (hNET) gene. A new intron of 476 base pairs was found in the middle of the 5â²-untranslated leader sequence and was shown to robustly enhance the promoter activity. Here, we show that the first hNET intron enhances both the homologous hNET and the heterologous thymidine kinase promoter activities in an orientation- and position-dependent manner. The first hNET intron exhibited a similar promoter-enhancing effect in both SK-N-BE(2)C (NET-positive) and HeLa (NET-negative) cell lines, showing that its function is not cell-specific. Transient transfection assays of a series of deletional constructs show that the first hNET intron contains subdomains with either positive or negative regulatory functions. Furthermore, DNase I footprinting analysis demonstrated that the 5â² side of the intron, encompassing the splice donor site, is prominently protected by nuclear proteins isolated from both SK-N-BE(2)C and HeLa cells. The protected nucleotide sequence contains a consensus E-box motif, known to regulate diverse eukaryotic genes, which overlaps with the splice donor site of the first intron. We demonstrate that two basic helix-loop-helix proteins, upstream stimulatory factors 1 and 2, are major proteins interacting at this site and that the E-box is at least in part responsible for the promoter-enhancing activity of the first intron. Furthermore, site-directed mutagenesis of the splice donor site of the first intron affects both correct splicing and transcriptional activity. Taken together, our results indicate that a cis -element residing at the first exon/intron junction, encompassing an E-box motif, has a unique dual role in basal transcriptional activation and splicing of hNET mRNA.